2015
DOI: 10.1080/00224499.2014.918085
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Drug Misuse and Sexual Behavior Among Young Adults

Abstract: Though research indicates a complex link between substance use and sexual risk behavior, there is limited research on the association between sexual risk behavior and prescription drug misuse. In light of the alarming increases in prescription drug misuse and the role of demographic characteristics in sexual risk behavior and outcomes, the current study examines demographic differences (gender, sexual identity, age, relationship status, parental class background, and race/ethnicity) in sexual risk behavior, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…Impaired mental health can lead to increased health risk behavior, such as alcohol and drug abuse [ 26 , 27 ]. Substance use was defined as a longitudinal predictor of risky sexual behavior [ 12 , 15 , 28 , 29 ] and was found to be significantly associated with an increased risk of the incidence of HIV infection [ 30 ]. Sex while under the influence of drugs was found to be prevalent among migrants, especially males [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired mental health can lead to increased health risk behavior, such as alcohol and drug abuse [ 26 , 27 ]. Substance use was defined as a longitudinal predictor of risky sexual behavior [ 12 , 15 , 28 , 29 ] and was found to be significantly associated with an increased risk of the incidence of HIV infection [ 30 ]. Sex while under the influence of drugs was found to be prevalent among migrants, especially males [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants reported going to hidden places away from parents and homes to use drugs, party and indulge in sexual activity. These findings have been documented in other empirical studies showing that young boys and girls use drugs like marijuana and alcohol, which may affect their decision-making [42], and invariable lead to risky behaviors including anal sex [43][44][45][46], violence [47][48][49][50][51], unprotected sex [52], and having casual and/or opportunistic sex [53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 57%
“…For example, a study in Dijon, France, found higher incidences in women but was perhaps linked to increased smoking use; a Barcelona study showed that more men presented with ICH but 3-month mortality did not differ; and the Global Burden of Diseases 2010 study found that hemorrhagic stroke occurs disproportionately among those <65 years from low-income countries [21][22][23]. However, younger men <30 years of age are more likely to engage in higher risk behavior and may increase their risk profile [24]. While physiological differences between sexes are typically uncontrollable, behavioral risk factors are modifiable and timely identification of traditional cardiovascular risk factors could aid in primary prevention of ICH.…”
Section: Discussion/conclusionmentioning
confidence: 99%